Emotion, Sound, and Piety: Interpreting the Living Qur’an through Anna M. Gade’s Thought in Indonesia - Nurlela, Ela; Dalila, Haula Hasna; Parlina, Iin; Safruroh, Safruroh (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2025)
This study explores the concept of the Living Qur’an in Indonesian society through the lens of Anna M. Gade’s thought, focusing on the ways in which Muslims read, interpret, and practice the Qur’an within social and cultural contexts. Employing a descriptive qualitative method based on literature analysis, the research investigates how the Qur’an functions not only as a source of doctrinal knowledge but also as a performative and emotional force in everyday religious life. Findings highlight the unique Indonesian engagement with the Qur’an, where non-Arabic speaking communities demonstrate profound aesthetic and spiritual connections through recitation and ritual. Gade’s analysis emphasizes the role of affect, sound, and embodiment in Qur’anic practices, offering an alternative perspective on piety as a deeply personal and experiential phenomenon. While her work is subject to critique—particularly regarding generalizations and lack of empirical specificity—it provides valuable insights into the religious dynamics of Indonesian Muslims, including community participation, media usage, lifelong learning, and women’s empowerment. The study concludes that the Qur’an operates both informatively and performatively, shaping a psycho-emotional relationship that influences the believer’s psychological and spiritual state. Gade’s contributions pave the way for future inquiries into the affective and performative dimensions of Islamic religiosity in diverse cultural settings. Studi ini mengkaji konsep Al-Qur’an yang Hidup dalam masyarakat Indonesia melalui pemikiran Anna M. Gade, dengan fokus pada cara umat Islam membaca, menafsirkan, dan mengamalkan Al-Qur’an dalam konteks sosial dan budaya. Menggunakan metode kualitatif deskriptif berbasis analisis kepustakaan, penelitian ini menelusuri bagaimana Al-Qur’an berfungsi tidak hanya sebagai sumber pengetahuan doktrinal, tetapi juga sebagai kekuatan performatif dan emosional dalam kehidupan keagamaan sehari-hari. Temuan menunjukkan bahwa keterlibatan masyarakat Indonesia dengan Al-Qur’an bersifat unik, di mana komunitas yang tidak berbahasa Arab tetap menunjukkan keterhubungan estetis dan spiritual yang mendalam melalui tilawah dan ritual. Analisis Gade menekankan peran afeksi, bunyi, dan tubuh dalam praktik-praktik Qur’ani, serta menawarkan perspektif alternatif tentang kesalehan sebagai fenomena yang sangat personal dan pengalaman. Meskipun pemikirannya mendapat kritik—terutama terkait generalisasi dan kurangnya data empiris yang spesifik—karyanya memberikan wawasan berharga mengenai dinamika keberagamaan Muslim Indonesia, termasuk partisipasi komunitas, pemanfaatan media, pembelajaran sepanjang hayat, dan pemberdayaan perempuan. Studi ini menyimpulkan bahwa Al-Qur’an memiliki fungsi informatif dan performatif sekaligus, membentuk hubungan psiko-emosional yang memengaruhi kondisi psikologis dan spiritual seorang Muslim. Kontribusi Gade membuka ruang bagi penelitian lanjutan terkait dimensi afektif dan performatif dalam keberagamaan Islam di berbagai konteks budaya.